Feeding responses of Crassostrea gigas (Thunberg) to inclusion of different proportions of toxic dinoflagellates in their diet - Bardouil, Michele; Bohec, Madeleine; Bougrier, Serge; Lassus, Patrick; Truquet, Philippe (Gauthier-villars/editions Elsevier, 1996)
An experimental flow-through system allowing determination of the feeding behaviour of individual molluscs was used to study oysters exposed to mixed diets composed of varying proportions of the diatom Thalassiosira weissflogii and two strains (toxic and nontoxic) of the dinoflagellate Alexandrium larnarense. Our results show that, when compared to a T. weissflogii unialgal diet, even a diatomltoxic dinoflagellate ratio as low in biomass as 90/10 reduced clearance rates and biodeposit production by oysters. Consumption was slightly but significantly decreased for a 50/50 diatomltoxic dinoflagellate mixture. For the toxic dinoflagellate unialgal diet, ingestion, absorption and consumption were completely inhibited. Thus, the inclusion of low amounts of toxic A. lamarense in a diet composed of T. weissflogii significantly altered pseudofaeces production and probably oyster filtering capacity , whereas no significant effect was observed with the non-toxic dinoflagellate. A l'aide d'un dispositif expérimental en circuit ouvert permettant de mesurer le comportement alimentaire individuel de bivalves, des huîtres (Crassostrea gigas) ont été exposées à des régimes alimentaires mixtes comprenant des proportions variables de la diatomée Thalassiosira weissflogii et de deux souches, l'une toxique, l'autre non toxique, du dinoflagellé Alexandrium ramarense. Les résultats montrent que même pour un rapport aussi faible que 90/10 en biomasse du régime diatomée / dinoflagellé toxique, le taux de filtration et la production de biodépôts sont réduits par rapport au témoin (diatomée seule). La consommation n'est diminuée de façon significative que pour un melange 50/50 du même mélange tandis que l'ingestion, l'absorption et la consommation sont complétement inhibés pour un régime composé uniquement du dinoflagellé toxique. Il apparaît donc que l'introduction, même faible, d'Alexandrium toxique dans un régime constitué de T. weissflogii altère la capacité des huîtres à produire des pseudofèces et probablement aussi. à filtrer, ...